1998
DOI: 10.1002/hep.510270241
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid synthesis in primary cultures of rat and human hepatocytes

Abstract: The regulation of hepatic bile acid formation is incompletely understood. Primary cultures of mammalian hepatocytes offer an opportunity to examine putative regulatory factors in relative isolation. Using rat and human hepatocytes in primary culture, we examined bile acid composition and the expression of the rate-limiting enzyme of formation, cholesterol 7␣-hydroxylase. Control rat hepatocytes showed a declining bile acid production over 4 days, from 156 ؎ 24 ng/mL (67% cholic acid) on day 1 to 55 ؎ 11 ng/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 46 publications
6
34
1
Order By: Relevance
“…GC acutely enhances hepatic gene expression of Cyp7a1 (27,28) and Cyp27 (12) in cultured hepatocytes. Surprisingly, neither Cyp7a1 gene expression nor activity was decreased upon adrenalectomy in rats (29).…”
Section: Discussionmentioning
confidence: 99%
“…GC acutely enhances hepatic gene expression of Cyp7a1 (27,28) and Cyp27 (12) in cultured hepatocytes. Surprisingly, neither Cyp7a1 gene expression nor activity was decreased upon adrenalectomy in rats (29).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids from cell culture media were measured as described previously (Ellis et al, 1998). Trimethylsilyl ether derivatives were analyzed by gas chromatography/mass spectrometry (Column HP-1, 6890N GC System, 5973 Mass Selective Detector; Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…11,12 We have found that primary human and rat hepatocytes in culture exhibit significant species differences in both types of bile acids formed and, more importantly, in the regulation of bile acids homeostasis. 13 We have also shown that primary human hepatocytes conjugate all secreted CA and CDCA by amidation to glycine or taurine 13,14 and thus, no unconjugated bile acids are found in the media.…”
mentioning
confidence: 88%
“…13 Briefly, 500 ng of deuterium-labeled CA and CDCA was added to 1 ml of cell culture medium. The mixture was hydrolyzed in 1 M KOH at 120 8C overnight.…”
Section: Analysis Of Bile Acidsmentioning
confidence: 99%